2019
DOI: 10.1177/0013916518812925
|View full text |Cite
|
Sign up to set email alerts
|

Spread the Green Word: A Social Community Perspective Into Environmentally Sustainable Behavior

Abstract: Engagement in proenvironmental behavior can be understood in part by considering how individuals operate as members of social communities and are influenced by these communities. In the present work, we use social network analysis to explore how social network structure predicts proenvironmental behavior. We consider three types of behaviors—(a) private, (b) public nonorganizational, and (c) organizational behaviors—and consider the potential for (i) behavioral diffusion and (ii) two types of opinion leader in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 71 publications
3
24
0
Order By: Relevance
“…This can lead to pluralistic ignorance, a situation in which people privately reject a norm (such as driving SUVs) but go along with it because they falsely assume that most others accept it. For example, Americans hold the inaccurate belief that a majority of their fellow citizens do not care much about mitigating climate change 27 , and are overly pessimistic about the views of conservatives on climate change 28 . A study conducted with a representative sample in the USA suggests that part of the reason why the poorest and ethnic minorities are underrepresented in environmental organisations and US government environmental agencies is the widespread false belief that they are not interested in environmental protection 29 .…”
Section: Pluralistic Ignorancementioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to pluralistic ignorance, a situation in which people privately reject a norm (such as driving SUVs) but go along with it because they falsely assume that most others accept it. For example, Americans hold the inaccurate belief that a majority of their fellow citizens do not care much about mitigating climate change 27 , and are overly pessimistic about the views of conservatives on climate change 28 . A study conducted with a representative sample in the USA suggests that part of the reason why the poorest and ethnic minorities are underrepresented in environmental organisations and US government environmental agencies is the widespread false belief that they are not interested in environmental protection 29 .…”
Section: Pluralistic Ignorancementioning
confidence: 99%
“…Credibility comes both from the source promoting the social norm and from the content of the norm 34 . People are more sensitive to social norms when they are promoted by leaders in their community 27 or when the individuals promoting the norm have themselves adopted the behavior. For example, a study of a programme that promotes residential solar panel installation in 58 towns in the United States found that community organizers who themselves installed panels through the programme recruited 62.8% more residents to install solar panels than community organizers who did not 35 .…”
Section: Credibility Of Normsmentioning
confidence: 99%
“…We recognize that this disciplinary mindset is also present in other social sciences and therefore the resulting methods, theories, assumptions, and statistics used can create a barrier and may limit the application to nexus issues. Examples of exceptions include using computers (microworlds) to understand natural resource decision‐making (Chen & Bell, ), using social network analysis to explore how social network structure is related to pro‐environmental behavior (Geiger, Swim, & Glenna, ), and understanding different tendencies to think in terms of systems (Ballew, Goldberg, Rosenthal, Gustafson, & Leiserowitz, ). Understanding what can be gained by system approaches to studying pro‐environmental actions could generalize to understanding what can be beneficial about studying the FEW nexus, perhaps particularly if one integrates human systems within the FEW nexus.…”
Section: Potential Barriers To Participation For Psychology Researchersmentioning
confidence: 99%
“…They emphasized that human behaviors play an important role in the ecosystem and called on researchers to pay attention to human environmental behavior and changes of such behaviors. To date, scholars have labeled PEB by using different terms, such as Environmentally responsible behavior (Lee et al, 2013 ; Su & Swanson, 2017 ; Cheung et al, 2019 ), Environmentally sustainable behavior (Kurz et al, 2007 ; Juvan & Dolnicar, 2014 ; Geiger et al, 2019 ), Environmental significant behavior (Stern, 2011 ; Bratt et al, 2015 ; Moon et al, 2017 ), Green behavior (Gordon-Wilson & Modi, 2015 ; Li et al, 2018 ; Kim et al, 2019 ), Ecological behavior (Testa et al, 2015 ; Otto & Pensini, 2017 ; Liu et al, 2019b ). Environmentally friendly behavior (Alp et al, 2008 ; Liobikiene et al, 2017 ; McCoy et al, 2018 ), etc.…”
Section: Introductionmentioning
confidence: 99%